Pemberdayaan Masyarakat melalui Pembuatan Ovitrap sebagai Upaya Pengendalian Vektor Demam Berdarah di Kelurahan Sawa, Kabupaten Konawe Utara, Provinsi Sulawesi Tenggara - Rahman Rahman; Putu Eka Meiyana Erawan; Siti Fatimah Zahrani; Sitti Fadhila Zulfahmi; Desrianti Desrianti; Fitri Aryaningsih; Aprilia Maharani; Muh. Zhaldri; Tri Mukti Ramadhan; Elsa Natasya Syafruddin; Rizki Amalya Putri; Putri Apriliani; Delviana Dewi; Nila Ayu Ashari; Tri Indah Sarawati; Zaskia Amalia Putri; Azzahra Zalzabila J; Anti Aprilia (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aimed to control the population of Aedes aegypti mosquitoes, which are the main vector of Dengue Hemorrhagic Fever (DHF), through the making and utilization of ovitraps in Sawa Village, Sawa District, North Konawe Regency. The methods applied in this program included field observation and door-to-door socialization to the community regarding the function, benefits, and procedure of making ovitraps. The socialization was designed to provide practical knowledge and raise awareness among residents about the importance of preventing mosquito breeding as part of DHF control efforts. A total of 30 households were involved as direct participants in this activity, and 30 ovitrap units were successfully made and distributed evenly to each household. The results showed that the community responded enthusiastically and expressed interest in adopting the ovitraps as a preventive measure. In addition, participants reported gaining new understanding about their active role in maintaining environmental health and reducing the risk of DHF transmission. The involvement of the community not only ensured that the ovitraps were effectively utilized, but also encouraged sustainable behavior in mosquito control practices. Overall, this program demonstrated that simple, low-cost, and community-based interventions such as ovitraps, combined with education and awareness campaigns, can contribute significantly to reducing the breeding sites of Aedes aegypti mosquitoes and lowering the potential spread of DHF in endemic areas.